Women’s descriptions of childbirth trauma relating to care provider actions and interactions - Reed, Rachel (BMC Pregnancy Childbirth, 2017)
BACKGROUND: Many women experience psychological trauma during birth. A traumatic birth can impact on postnatal mental health and family relationships. It is important to understand how interpersonal factors influence women’s experience of trauma in order to inform the development of care that promotes optimal psychosocial outcomes. METHODS: As part of a large mixed methods study, 748 women completed an online survey and answered the question ‘describe the birth trauma experience, and what you found traumatising’. Data relating to care provider actions and interactions were analysed using a six-phase inductive thematic analysis process. RESULTS: Four themes were identified in the data: ‘prioritising the care provider’s agenda’; ‘disregarding embodied knowledge’; ‘lies and threats’; and ‘violation’. Women felt that care providers prioritised their own agendas over the needs of the woman. This could result in unnecessary intervention as care providers attempted to alter the birth process to meet their own preferences. In some cases, women became learning resources for hospital staff to observe or practice on. Women’s own embodied knowledge about labour progress and fetal wellbeing was disregarded in favour of care provider’s clinical assessments. Care providers used lies and threats to coerce women into complying with procedures. In particular, these lies and threats related to the wellbeing of the baby. Women also described actions that were abusive and violent. For some women these actions triggered memories of sexual assault. CONCLUSION: Care provider actions and interactions can influence women’s experience of trauma during birth. It is necessary to address interpersonal birth trauma on both a macro and micro level. Maternity service development and provision needs to be underpinned by a paradigm and framework that prioritises both the physical and emotional needs of women. Care providers require training and support to minimise interpersonal birth trauma.